2022
DOI: 10.1159/000525880
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Stroke Burden in Central and Eastern Europe from 1990–2019

Abstract: <b><i>Introduction:</i></b> There has been wide recognition of the health divide between Western Europe and the former socialist countries from Central and Eastern Europe. However, these have not been assessed in terms of burden of disease, and the effect of stroke has not been fully elucidated, especially in terms of time trends. <b><i>Methods:</i></b> The West-Eastern European stroke burden was analysed using data from the Global Burden of Stroke (GBD) Study 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 25 publications
1
0
0
Order By: Relevance
“…The DALYs rate for diet-induced stroke showed a decreasing trend in all age groups among the member countries in Europe. Dokova et al ( 38 ) found that ASR of stroke DALY declined in West, Central, and East Europe regions and in all twenty East and Central European countries but at a different pace, which is consistent with our study. For those aged 50–74, the DALYs for stroke due to dietary risk factors in all other “B&R” member countries showed a decreasing trend, except for the Philippines, which rose and Turkmenistan, which remained stable.…”
Section: Discussionsupporting
confidence: 93%
“…The DALYs rate for diet-induced stroke showed a decreasing trend in all age groups among the member countries in Europe. Dokova et al ( 38 ) found that ASR of stroke DALY declined in West, Central, and East Europe regions and in all twenty East and Central European countries but at a different pace, which is consistent with our study. For those aged 50–74, the DALYs for stroke due to dietary risk factors in all other “B&R” member countries showed a decreasing trend, except for the Philippines, which rose and Turkmenistan, which remained stable.…”
Section: Discussionsupporting
confidence: 93%
“…This distinctive trend raises concerns among health professionals and policymakers, highlighting unique challenges in this transitional nation [28]. According to the literature, all Central and East European countries experienced a decline in all-cause disease burden between 1990 and 2019, and a gap was confirmed between the East, the Central, and the West European region for men but not for women [29]. The WHO estimated that non-communicable diseases (NCDs) account for about of 90% of the deaths in Albania and the probability of dying between ages 30 and 70 years from the 4 main NCDs is about 19%.…”
Section: Discussionmentioning
confidence: 99%
“…Age-standardized disabilityadjusted life years lost (DALYs) for stroke declined in the three European regions and in all twenty Central and Eastern European countries, but at different rates. Lost years of life (YLL) accounted for more than 70% of DALYs for stroke and more than 90% of DALYs for men in Eastern European countries [26].…”
Section: Discussionmentioning
confidence: 99%